2003
DOI: 10.2337/diabetes.52.9.2441
|View full text |Cite
|
Sign up to set email alerts
|

Level of an Advanced Glycated End Product Is Genetically Determined

Abstract: Reducing sugars react with amino groups in proteins, lipids, and nucleic acids to produce advanced glycation end products (AGEs), including N ⑀ -carboxymethyl lysine (CML), which have been implicated in oxidative stress and vascular damage. The aim of this study was to determine whether genetic factors influence serum CML levels in normal subjects. We performed a classical twin study of CML in healthy nondiabetic female twins, 39 monozygotic and 45 dizygotic pairs, aged 21-74 years. Serum CML levels were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 21 publications
3
33
0
4
Order By: Relevance
“…This has also been shown in mouse models (4). Finally, a study of monozygotic and dizygotic twins and northern European children revealed that environmental AGEs, likely from the diet, are important in the development of type 1 diabetes mellitus (D. Leslie, unpublished observations) (12).…”
Section: Introductionmentioning
confidence: 70%
“…This has also been shown in mouse models (4). Finally, a study of monozygotic and dizygotic twins and northern European children revealed that environmental AGEs, likely from the diet, are important in the development of type 1 diabetes mellitus (D. Leslie, unpublished observations) (12).…”
Section: Introductionmentioning
confidence: 70%
“…57 Associados aos processos de formação, absorção e detoxificação, fatores genéticos podem influenciar o metabolismo de AGEs nos indivíduos e, consequentemente, a predisposição para o desenvolvimento de patologias associadas a estes compostos. 4,59 AGEs/ALEs em alimentos A dieta é considerada a principal fonte exógena de AGEs/ALEs e, embora haja um importante corpo de evidências associando a ingestão desses compostos à promoção de diversas disfunções metabólicas que preocupam as autoridades de saúde em todo o mundo, existem ainda muitas lacunas neste campo de pesquisa que suscitam debates e crescentes investigações envolvendo, especialmente, os mecanismos de absorção e biodisponibilidade dos AGEs/ALEs dietéticos. 60,61 Sabe-se claramente que a taxa de formação e a diversidade de AGEs nos alimentos dependem de vários fatores, sendo o tempo e temperatura de processamento, concentração de reagentes, disponibilidade de água e pH particularmente bem reconhecidos como fatores decisivos na taxa de reação do tipo Maillard.…”
Section: Figura 3 Estruturas De Produtos Finais De Glicação Avançadaunclassified
“…Glycated collagen has been shown to accumulate at a rate of 3.7% per year (36), percentage highly infl uenced by environmental factors such as diet and smoking (37). Moreover, studies conducted on healthy twins, both monozygotic and heterozygotic, concluded that circulating AGEs level's are genetically determined (38).…”
Section: Factors Involved In Glycationmentioning
confidence: 99%